Results of Treatment of the Multiple Ligament Injured (Dislocated) Knee. Issue 3 (September 2020) - James, Evan W.; Wolfe, Isabel; Marx, Robert G.
Abstract : Knee dislocations leading to multiligament knee injuries are associated with a wide variety of bony, ligamentous, soft tissue, and neurovascular injury patterns. Numerous management strategies have been proposed including nonoperative treatment and surgical repair or reconstruction. In recent years, an emphasis has been placed on anatomic repair and reconstruction principles, which have shown superior outcomes compared with older techniques. However, despite these advances, clinical outcomes continue to vary widely, with many patients experiencing chronic pain, stiffness, loss of range of motion, instability, and failure to return to work or sports. The purpose of this chapter is to review clinical outcomes following combined anterior and posterior cruciate ligament, medial collateral ligament, and posterolateral corner injuries sustained during a knee dislocation. Understanding the available treatment options and reported outcomes will allow surgeons to individualize management to address each patient's specific injury pattern and functional goals.